DINAMIKA PENERJEMAHAN AL-QUR’AN DI KALANGAN ORIENTALIS - Ekatul Hilwatis Sakinah; Syahidil Mubarik Mh (EL-ADABI : Jurnal Studi Islam, 2024)
The translation of the Qur'an into various languages is not only done by Muslims, but non-Muslims  (orientalists) also participate in translating it. There was a very long polemic during the translation of the Qur'an. The purpose of this research is to elaborate on the role and development of the Qur'an translation among orientalists that later gave birth to the characteristics (model) of translation. This research uses descriptive analytical method with library research. The data were obtained through books, articles, journals, and other writings related to the research theme. The results show that there are three characteristics of translation in the role and development of al-Qur'an translation by orientalists. First, the translation was aimed at undermining Islam. This lasted from the 12th century AD to the 17th century AD. Second, the translation of the Qur'an began to reduce the elements of hatred against Islam and they began to be open to the corpus of Muslim interpretations, although there were still few traces of their predecessors. This period lasted from the 17th century to the 19th century, and it should be noted that the 18th century became the starting point of the translation paradigm shift. Third, the translation of the Qur'an that has begun to be objective. Third, the translation of the Qur'an that has been friendly and objective. The 9th century until now is a bright spot for orientalists who translate the Qur'an. Many of the orientalists began to be open and gentle in explaining Islam, they also often use Muslim interpretations as a reference. In fact, some of them when explaining Islam there are trying to defend Islam from the attacks of previous orientalists.